Patterns and predictors of intimate partner violence among married women living in urban informal settlements of Bangladesh: A cross-sectional survey (Bangabandhu Sheikh Mujib Medical University Journal, 2025)
Background: Despite legal and policy proscriptions, intimate partner violence remains a pervasive issue worldwide, with particularly severe implications for marginalised and vulnerable women. In Bangladesh, women living in urban slums may face increased risks, but evidence remains limited. This study aimed to address this knowledge gap.Methods: Cross-sectional survey was done among ever-married women resident (aged 18 years or older) in slums-dwelling in Dhaka North, Dhaka South and Gazipur. Data was collected using face-to-face interview on four types of intimate partner violence: physical, sexual, emotional and economic. Univariate and multivariate logistic regression analyses were done to explore the association between the violence outcome variables and sociodemographic characteristics.Results: Six hundred seven women participated in the survey. The overall level of any form of life-time violence was 82%. Physical violence was most reported (66%), followed by economic (47%), sexual (44%), and emotional (38%). Uneducated women, and those whose husbands were uneducated, faced particularly high risks of violence. Gazipur stood out as an area with higher intimate partner violence than other slum areas. Working women also experienced more life-time violence than non-working women.Conclusion: Urban slum women face high levels of violence in Dhaka and Gazipur. Policy level interventions, workplace-based actions and community-level measures should be taken to curb this epidemic. Specific steps should be taken to increase awareness related to intimate partner violence, and improve attitudes towards gender roles among women residing in urban slums.